Quality of Life among Postnatal Mothers attending Immunization Clinic of a Tertiary Level Hospital - Budhathoki, Roshina; Ghimire, Binda (Journal of Karnali Academy of Health Sciences, 2022)
Background: Postnatal period is a transition period marked by physical, emotional and relationship changes. Yet, the mostneglected period than before and during childbirth as stated by World Health organization (WHO). Quality of Life (QOL) is anindividual's perception of their position in life in relation to their goals and expectations that indicates unmet needs and interventionoutcomes. Demands made by childbirth on mother’s wellbeing can lead to poor QOL in postnatal period. Thus, the objective ofthe study was to identify QOL among postnatal mothers.Method: Descriptive cross-sectional research design was used to find QOL. 217 postnatal mothers were selected usingconvenience sampling technique. Data was collected using structured interview schedule containing WHOQOL-BREFquestionnaires. Data analysis was done using descriptive statistics i.e. frequency, percentage, mean and standard deviation tosummarize data and inferential statistics i.e. independent t-test and one way ANOVA to compare domain scores with selectedvariables.Result: The highest mean score was on social relationship domain (70.06 ± 14.62) denoting highest QOL in this domain, followedby psychological (68.36 ± 17.90), Physical (67.08 ± 24.79) and environment domain (64.38 ± 16.59) respectively. Significantdifference was found between domain scores and age, education, pregnancy type, ANC visit, delivery type, perineal trauma(p